Macrophages as key modulators of calcific aortic valve disease - Issa, Nervana; Blot, Gérémy; Candellier, Alexandre; Boudot, Cédric; Louvet, Loïc; Kamel, Saïd; Bennis, Youssef; Hénaut, Lucie (Frontiers in Cardiovascular Medicine, 2025)
Calcific aortic valve disease (CAVD), defined by thickening, fibrosis, and mineralization of the aortic valve (AV) leaflets, is the most common valvular heart disease worldwide. This progressive remodeling gradually impairs valve opening, obstructing blood flow. Without intervention, the resulting aortic stenosis (AS) causes hemodynamic deterioration that ultimately leads to heart failure and death. To date, therapeutic options remain limited, making valve replacement the reference treatment. While valvular endothelial and interstitial cells have traditionally been considered the primary drivers of the osteogenic program underlying AV remodeling, recent evidence highlights a central role for macrophages, whose plasticity profoundly impacts the local microenvironment. In their inflammatory state, macrophages release cytokines, generate oxidative stress, and secrete Bone Morphogenetic Protein 2 (BMP2), which promotes the osteogenic transformation of valvular cells. The resulting calcium crystal deposition further amplifies macrophage-driven inflammation, creating a vicious cycle. Conversely, immunomodulatory macrophages can protect against CAVD by releasing pyrophosphate, a calcification inhibitor. However, these macrophages also secrete pro-fibrotic factors and may undergo myeloid-to-mesenchymal transition, processes that paradoxically contribute to AV fibrosis and mineralization. In addition, macrophages within the AV can differentiate into osteoclast-like cells, suggesting that a bone-like remodeling process occurs in the cardiovascular wall. This high phenotypic plasticity complicates our understanding of CAVD pathogenesis and highlights the need for deeper insight into macrophage functions to design effective preventive and therapeutic strategies. This review summarizes the mechanisms through which different macrophage subsets promote, prevent, or reverse AV remodeling, in both native and bioprosthetic contexts, and explores the therapeutic potential of targeting macrophages or their activity to slow AS progression.